Leadership and organizational climate of a Cuban pediatric hospital. Vision of head and care nurses - Annia Lourdes Iglesias Armenteros; Julia Maricela Torres Esperón; Yuliett Mora Pérez; Jose Rolando Sánchez Rodríguez (Universidade Federal de Santa Maria, 2020)
Objective: Describe experiences of nurses heads and clinical nurses on the causes that may affect the organizational climate of pediatric services in a Cuban hospital. Method: Qualitative and exploratory study done in the months of April - December, 2018 with 14 heads nurses and 11 healthcare nurses, belonging to the Pediatric University Hospital "Paquito Gonzales Cueto", Province of Cienfuegos, Cuba. The data were collected with the focus group technique; the narratives were processed through content analysis based on the theoretical framework of organizational climate with the central category of leadership. The research was evaluated by the Ethical-Scientific Committee of the reference hospital. Results: Four subcategories of content analysis emerged based on the theoretical framework. The most important was "ideology of a manager "followed by "continuous improvement" "listening for relational harmony" and "sense of belonging". Conclusions: the main causes as affecting organizational climate are related to the characteristics of the leader and the possibilities of overcoming them and the rest of the staff.